Stenting technique for critical congenital heart defects with obstruction of pulmonary blood flow - Polivenok, I. (Ukrainian Journal of Cardiovascular Surgery, 2017)
Management of critical congenital heart lesions with pulmonary flow obstruction in the neonatal period presents numerous challenges. Endovascular stenting of the ductus arteriosus (DA) in ductal-dependent pulmonary circulation or right ventrical outflow tract (RVOT) as an alternative to the aorto-pulmonary shunt has become increasingly popular in the last years. The procedural aspects of the reverse anchor-wire technique for DA or RVOT stenting is described by author.